Al-Shadru and Its Relationship with Psychology - Luky Priyanto (Universitas Islam Balitar, 2022)
Al-Quran is the word of Allah SWT that was revealed to the Prophet Muhammad SWT which can be a means of worship for anyone who reads it. Al-Quran is a guide for all Muslims and the followers of the Prophet Muhammad SAW. Al-Quran was revealed by Allah SWT to the Arabs in Arabic. Arabic is well-known for its numerous word derivations. One of the words in Al-Quran is Al-Shadru, which means ‘chest’. It is the body cavity where the heart and lungs reside. There are two forms of the word shadru in Al-Quran, namely fi’il (verb) and isim (noun). Shadru as a verb contains 2 words: yhasdiru and yashdira. Shadru as a noun comprises 44 words; some of them include shadran, shadrahu, shadruka, as-shudur, shadri, shuduruhum, and shudurikum. The concept of shadr corresponds to Sigmun Freud’s theory that humans consist of the id, ego, and superego. The ego desires for pleasure will always be bridged by the superego to measure whether they are good or bad. In Islam, the process of thinking involves many elements of the brain/reason, lust, and conscience/Qolb. In addition to the id, ego, and superego, the concept of Al-Shadru is also in line with Daniel Golemen’s theory about emotional intelligence.